2023
DOI: 10.1149/2162-8777/ad161d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural, Optical and Optoelectrical Properties of the Chemically Deposited Cu2BaGeS4 Thin Films

Abdullah Alsulami,
Ali Alsalme

Abstract: In this work, thin films of copper barium germanium sulfide (Cu2BaGeS4) were generated via the chemical bath deposition technique. The X-ray diffractometer identified the Cu2BaGeS4 layers’ crystal structure. It showed that the Cu2BaGeS4 films have a hexagonal structure. The EDAX results demonstrated stoichiometric composition, which validated the composition of the Cu2BaGeS4 layers. However, the Cu2BaGeS4 sheets under investigation showed a direct energy gap, as demonstrated by the linear optical analysis, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The optoelectrical indices of the ZnSb 2 O 4 layers. Moreover, the relaxation time τ of the examined ZnSb 2 O 4 films can be estimated via this formula:73 …”
mentioning
confidence: 99%
“…The optoelectrical indices of the ZnSb 2 O 4 layers. Moreover, the relaxation time τ of the examined ZnSb 2 O 4 films can be estimated via this formula:73 …”
mentioning
confidence: 99%
“…It has been found that N m opt ( / * ) and L ε improve with increasing the Li contents. Additionally, the below relation can be used to estimate the relaxation period τ of the examined Li-doped ZTO 3 sheets:62…”
mentioning
confidence: 99%